Slower progression of amyotrophic lateral sclerosis with external application of a Chinese herbal plaster–The randomized, placebo-controlled triple-blinded ALS-CHEPLA trial - Sven Schröder; Mingzhe Wang; Dandan Sima; Joana Schröder; Joana Schröder; Xuying Zhu; Xuanlu Zheng; Lin Liu; Lin Liu; Tingying Li; Qiudong Wang; Thomas Friedemann; et al. (Frontiers in Neurology, 2022)
BackgroundAmyotrophic lateral sclerosis (ALS) is a chronic neurodegenerative disease characterized by gradually increasing damage to the upper and lower motor neurons. However, definitive and efficacious treatment for ALS is not available, and oral intake in ALS patients with bulbar involvement is complicated due to swallowing difficulties.Hypothesis/purposeThis study investigated whether the external plaster application of the herbal composition Ji-Wu-Li efficiently slows ALS progression because prior studies obtained promising evidence with oral herbal applications.Study designThe randomized, triple-blinded study compared the efficacy, safety, and tolerability of the application of Ji-Wu-Li plaster (JWLP) with placebo plaster (PLAP).MethodsIn total, 120 patients with definite ALS, clinically probable ALS, or clinically probable laboratory-supported ALS were randomized in a 1:1 ratio to receive JWLP or PLAP. Patients were treated and observed for 20 weeks. The primary outcome was the ALSFRS-R score, while the secondary outcomes were the ALS-SSIT score and weight loss.ResultsThe mean±SD decrease in the ALSFRS-R over 20 weeks differed by 0.84 points in a group comparison (JWLP, −4.44 ± 1.15; PLAP, −5.28 ± 1.98; p = 0.005). The mean increase in the ALS-SSIT over 20 weeks differed by 2.7 points in a group comparison (JWLP, 5.361.15; PLAP, 8.06 ± 1.72; p < 0.001). The mean weight loss over 20 weeks differed by 1.65 kg in a group comparison (JWLP, −3.98 ± 2.61; PLAP, −5.63 ± 3.17; p = 0.002). Local allergic dermatitis suspected as causal to the intervention occurred in 10 of 60 participants in the JWLP group and 9 of 60 participants in the PLAP group. Systemic adverse events were mild, temporary, and considered unrelated to the intervention.ConclusionThe JWLP showed clinical efficacy in the progression of ALS, as measured by the ALSFRS-R, ALS-SSIT, and weight loss in a randomized, placebo-controlled trial. Because skin reactions occurred in both groups, the covering material needs improvement. All of the Ji Wu Li herbal ingredients regulate multiple mechanisms of neurodegeneration in ALS. Hence, JWLP may offer a promising and safe add-on therapy for ALS, particularly in patients with bulbar involvement, but a confirmative long-term multicentre study is required.